Evaluation of Surface Free Energy of Various Fruit Epicarps Using Acid-Base and Zisman Approaches - Osorio-Lira, F; Skurtys-Olivier , F; Enrione, J (2011)
Surface free energy (SFE; ? SV) of 16 fruit epicarps present on the Chilean market was calculated by two approaches: the acid-base and Zisman. The results show that the fruit epicarps were low surface energy since the magnitude of ? SV falls within a narrow range, between 37 and 44 mJ m -2. Zisman approach gave a critical surface tension values, ? cr lower than the SFE calculated by the acid-base approach. Significant differences in SFE between the fruits may be explained by the variation in the chemical composition of epicuticular waxes. The polar (? AB SV) and apolar (? LW SV) components of the SFE were also calculated and a mathematical relation was between both values was found. Values of ? AB SV and ? LW SV could also be associated with the fruit family and the tissue origins in the ovary region. Finally, it has been shown that fruit epicarps exhibited predominantly electron-donator behaviour since ? - SV > ? + SV. We believe that the results reported here can potentially impact in food engineering because the compatibility of coatings and fruit epicarps depends on the interaction of their respective chemical and physical properties. © 2011 Springer Science+Business Media, LLC.